Configurable on-Chip Gel Electrophoresis in Inkjet 3D Printed Microfluidic Modules - Rafał Walczak; Krzysztof Adamski; Wojciech Kubicki (Proceedings, 2017)
Inkjet 3D printing is with success used for preparation microfluidics devices as a microfluidic chips for DNA separation. Utilized this technic help us to prepare a chip in shorter time and cheaper, but length of microchannel are limited by possibility of support material removing. One of the Solution for solve this limitations is divide a microfluidics chips for modules and printing them separately. I this paper we present a modular configurable system for gel electrophoresis. Results of carrying methylene-blue from first module to second module are showed. New methodology for electrophoresis is show.